Comparing psychopathology rates across autism spectrum disorders and intellectual disabilities. Issue 5 (5th November 2018) - Matthews, Martyn; Bell, Elliot; Mirfin-Veitch, Brigit
Abstract : Purpose: The purpose of this paper is to compare the rates and patterns of comorbid anxiety, depression and ADHD across people with: autism spectrum disorder (ASD) plus intellectual disability (ID), ASD/no ID (AS/HFA) and ID only. Design/methodology/approach: Data were obtained using structured file review and two psychometric screening instruments. File reviews used a modified version of the Case Review Protocol from the Diagnostic Criteria for Psychiatric Disorders for Use with Adults with Learning Disabilities. Screening employed the Reiss Screen for Maladaptive Behaviour and the ASD-Comorbidity-Adults scale. Findings: Levels of anxiety, depression and ADHD were high for all three groups, and greater than in general population studies. Between groups, the AS/HFA sample had significantly higher anxiety, while the ASD/ID group had significantly greater ADHD. Groups did not differ on measures of depression or total psychopathology. Levels of ADHD, but not anxiety or depression, increased with severity of ID and ASD symptoms. Research limitations/implications: More research is needed on the relationship between ASD and both anxiety and ADHD, particularly the identification of these comorbid conditions and their treatment. Practical implications: Rigorous screening for comorbid mental health conditions is required to achieve the best outcomes for adults with ASD. Originality/value: The study used a broader community-based sample than previous comorbidity research. Including adults with ID but without ASD enabled a comparison of types and rates of disorder across three distinct but related groups with neurodevelopmental disorders.